Kreativitas Dosen dalam Pembelajaran Daring selama Pandemi Covid-19 di STAI Hasan Jufri Bawean - M, Ansharuddin (International Conference on Islamic Studies, 2020)
Through the Circular of the Minister of Education and Culture of the Republic of Indonesia No. 3 of 2020 concerning the Prevention of COVID-19 in the Education unit, all higher education in Indonesia takes firm steps on the government's appeal to carry out learning activities from home. The policy of learning from home is also enforced at STAI Hasan Jufri Bawean, this is a new experience for both lecturers and students so that it attracts researchers to find out about the online learning system during the Covid-19 pandemic at STAI Hasan Jufri Bawean. This study aims to determine the creativity of online learning at STAI Hasan Jufri Bawean during the Covid-19 pandemic and to find out the various media used by lecturers in learning during the Covid-19 pandemic at STAI Hasan Jufri Bawean. This research includes field research (fiel reseach) conducted at STAI Hasan Jufri Bawean. The method used in this research is descriptive qualitative method. Data collection was carried out using interview, observation, and documentation methods. The results in this study are that a lecturer is required to be creative and adaptive to their needs and development so that they are able to answer the problems faced, for example by making a video presentation of course material which is then uploaded to google classroom and edmodo, as for online learning media used by lecturers, others are google classroom, edmodo, google meet, zoom meeting, WhatsApp group and gem4me group.